A 'Leader-full' Movement Under Authoritarianism: Mobilization Networks in Hong Kong’s Anti-Extradition Movement - Lai, Eric (Routledge, 2022)
Analysing Hong Kong’s 2019–2020 anti-extradition movement, this chapter suggests that despite the state’s attempts to disenfranchise it by capturing visible leaders, the movement evolved to be ‘leader-full’, or full of leaders. Traditional social movement organizations and pro-democracy lawmakers continued to mobilize resources but were no longer positioned as leaders. Local communities and individuals formed different mobilization networks to expand the movement’s scope and scale. Expressive protest actions and movement networks formed via social media made the anti-extradition movement more resilient in the face of state repression.